Philip Gibbs: war correspondent of a new dispensation - Woodward, Christina Anna (Rhodes University, Faculty of Humanities, Department of History, 1985)
The process of democratization which appeared in the nineteenth century was partly responsible for the emergence of a mass readership. It consisted of the new urban population which had its own tastes and interests, intellectual capacity and purchasing power. The popular press was firmly established by 1900 and it radically altered the scope and style of daily journalism in its attempt to speak in the language of the majority. Philip Gibbs was one of the prominent journalists between 1900 and 1914. His aspiration to become a war correspondent stemmed from the image of the war correspondent as a figure of romance and adventure, the consequence of the militarist spirit of the age and the licence which granted him freedom of movement. Inevitably, the war correspondent carne in conflict with the military which had not kept pace with democratization and sensed a challenge to itself and to national security. Censorship and restrictions on the war correspondent tightened, until major army reforms between 1901 and 1912 brought more cordial relations between the press and the military. When the Great War broke out in 1914 the co-operative atmosphere broke down as censorship was reinstated, more severely than before. It challenged the freedom of the press and the right of the people to know. Gibbs was determined that the people should have access to news from the front. He fought hard for that objective and was instrumental in the compromise reached between the military and the press when an officially recognized system was devised for press representation on the Western Front. The wisdom of such a move was shown by the success of Philip Gibbs' war correspondence, which had appeal to a mass readership in its own language and with subjects of interest to it.
Keywords: Gibbs, Philip, 1877-1962; War correspondents; War -- Press coverage; Mass media and war; Journalists